A new species of lizard genus Gymnodactylus Spix, 1825 (Squamata: Gekkota: Phyllodactylidae) from Serra do Sincorá, northeastern Brazil, and the status of G. carvalhoi Vanzolini, 2005 - Cassimiro, José; Rodrigues, Miguel T. (Zootaxa, 2009)
A new species of gekkonid lizard genus Gymnodactylus Spix, 1825 is described on the basis of material collected in the “campos rupestres” (open rocky communities) of Mucugê municipality, northeastern Brazil. G. vanzolinii sp. nov. differs from its congeners in the number of transverse and longitudinal rows of dorsal tubercles and color pattern. It is thought to be closer to G. guttulatus which also occurs and is restricted to the rocky communities from highland open areas in the Espinhaço mountain range. The discovery leads to a reevaluation of the taxonomic status of G. carvalhoi Vanzolini, 2005, which is here considered a synonym of G. amarali Barbour, 1925.